Basic Knowledge about Metal Stent Development - Seok Jeong (Korean Society of Gastrointestinal Endoscopy, 2016)
Biliary self-expandable metal stents (SEMS), a group of non-vascular stents, have been used in the palliative management of biliary obstruction around the world. However, there are still unmet needs in the clinical application of biliary SEMS. Comprehensive understanding of the SEMS is required to resolve the drawbacks and difficulties of metal stent development. The basic structure of SEMS, including the materials and knitting methods of metal wires, covering materials, and radiopaque markers, are discussed in this review. What we know about the physical and mechanical properties of the SEMS is very important. With an understanding of the basic knowledge of metal stents, hurdles such as stent occlusion, migration, and kinking can be overcome to develop more ideal SEMS.